Active Cryptococcus neoformans glucuronoxylomannan production prevents elimination of cryptococcal CNS infection in vivo - Vanessa Enriquez; Melissa E. Munzen; Luz M. Porras; Claudia L. Charles-Niño; Fahong Yu; Karina Alviña; Raddy L. Ramos; Michael R. Dores; Paola Giusti-Rodriguez; Luis R. Martinez (Journal of Neuroinflammation)
Abstract Background Cryptococcus neoformans (Cn) causes life-threatening meningoencephalitis in individuals with AIDS. Cn’s polysaccharide capsule is mainly composed of glucuronoxylomannan (GXM) and plays a key role in the dysregulation of immunity, resistance to antifungal drugs, and systemic dissemination, including CNS invasion. Although recent studies have begun to elucidate the involvement of microglia in cryptococcosis, our knowledge of these CNS resident phagocytes in the control of cryptococcosis is limited. Methods We investigated microglial responses to Cn infection and the effect of active capsular production by comparing wild-type H99 and acapsular mutant cap59 strains using the CX3CR1-EGFP transgenic mouse and a stereotaxic intracerebral infection model. Results Microglia had difficulty combating Cn H99 infection. Active production and secretion of the capsular material altered the morphology and distribution of microglia around cryptococcomas or fungal brain lesions. It also affected the infiltration of peripheral immune cells to CNS fungal infection. Moreover, RNA sequencing analyses supported the importance of capsule production in immune modulation. Chemotaxis assays demonstrated that active capsular production by Cn H99, and especially GXM, impaired microglial motility and fungal phagocytosis. Conclusion Our findings suggest that microglia may not be able to control cryptococcal CNS infection and that active capsular production and release may contribute to the progression and persistence of cerebral cryptococcosis.